Practicing Market Orientation for Customer Engagement: The Mediating Effect of Personalization and Multi-Channel Marketing - Saad Shahid; Rida Ayaz (The Lahore Journal of Business)
The purpose of this study is to examine whether an organization can create customer engagement by practicing market orientation, personalization and using multi-channel marketing. The proposed conceptual framework is empirically tested using quantitative data. Survey data were collected from 240 students of both private and public universities in Pakistan. The findings show support that market orientation and personalization do not lead to customer engagement but multichannel marketing does have a relationship with customer engagement. The proposed mediation of personalization and multi-channel marketing was not empirically supported. The results of this research suggest that firms should practice multi-channel marketing to interact with the target market. Multichannel marketing is most likely to keep the existing and potential consumers engaged. This study adds value to the literature by providing an explanation of the impact of the two inbound marketing themes; personalization and multi-channel marketing and their consequent relationship with customer engagement.